EFFECT OF TRANSPORT FATIGUE CHOICE ROUTE - , Н. У., Г. И. (Municipal economy of cities (Technical science), 2013)
Describes the relationship between the transport fatigue and its impact on the development of the passengers. If there are alternative routes, passengers choose the way in which the degree of fatigue less.